Sustainable Development of Mountain Sports Leisure Towns in China: Challenges, Strategies, and Lessons from International Best Practices - Chen, Hongbing; Wang, Xinghua (Technium Social Sciences Journal, 2025)
The development of mountain sports leisure towns represents a significant intersection of sports industry development, tourism innovation, and rural revitalization in China. This study examines the current state of China's mountain sports leisure towns, with a particular focus on development patterns, challenges, and opportunities for sustainable growth. Using a comparative case study approach, this research analyzes the development model of Chamonix-Mont-Blanc, France, which has evolved from a modest alpine village into a world-renowned mountain sports destination over two centuries. Drawing on recent data from 2023-2024, this study reveals that China's sports industry reached 3.67 trillion yuan (USD 513 billion) in total scale, with the sports leisure town sector contributing approximately 2.2 trillion yuan. However, Chinese mountain sports leisure towns face significant challenges including spatial planning inconsistencies, insufficient integration of local culture with sports tourism products, and underdeveloped industrial ecosystems despite resource concentration. Through systematic analysis of development patterns, this research identifies three critical strategies for Chinese mountain sports leisure towns: optimizing spatial layout and service infrastructure, emphasizing distinctive local cultural characteristics, and fostering deep industrial integration through value chain thinking. The findings contribute to the theoretical understanding of sports tourism development and provide practical implications for policymakers and industry stakeholders engaged in mountain sports leisure town development in emerging economies.